Developing Objective Metrics for Unit Staffing (DOMUS) study. Issue 9 (12th September 2014) - Siddiqui, I; Whittingham, B; Meadowcroft, K; Richardson, M; Cooper, J C; Belcher, J; Morris, E; Ismail, K M K
Abstract : Objective: Safe midwifery staffing levels on delivery suites is a priority area for any maternity service. Escalation policies are tools that provide an operational response to emergency pressures. The aim of this study was to assess the feasibility of using a scoring system to contemporaneously assess the required staffing level based on demand and use this to determine delivery suite escalation level and utilise the information generated regarding clinical activity (Demand) and staffing levels (Capacity) to generate unit-specific calculation for the actual number of midwifery staff required. Setting: A maternity unit of a university-affiliated tertiary referral hospital. Design: Over a 12-month period, specifically designed scoring sheets were completed by delivery suite shift co-ordinators four times a day (04:00, 10:00, 16:00 and 22:00). Based on the dependency score (Demand) and the number of midwifery staff available (Capacity), an escalation level was determined for each shift. The 80th centile of the demand was used to determine optimal capacity. Results: A total of 1160 scoring sheets were completed. Average staff number throughout the year on any shift was 7 (range 3–11). Average dependency score was 7 (range 1–14). The 80th centile for demand was calculated to be 11. Conclusions: This study stresses the importance and usefulness of a simple tool that can be used to determine the level of escalation on delivery suite based on an objective scoring system and can also be used to determine the appropriate staffing on delivery suite.